Heidegger's Prognostic: Originary thinking at the end of philosophy of education. Issue 8 (2nd July 2016) - Duarte, Eduardo
Abstract: This article is one in a series of attempts to clear discursive space for speculative thinking in education. The impulse to move toward another form of 'philosophy of education' is inspired by ongoing conversation with Heidegger, whose later work, in particular, indicated the possibility of a poetic thinking that could express the state of wonder from whence learning arises. Philosophers of education may be interested in the organized manner in which learning is organized at the level of culture, politics, and society. Speculative thinking in education, however, makes a horizontal transcendence, into an imagined future beyond the apparent present. In what follows, I will explore what I am calling Heidegger's prognostic in order to make further articulation of the project of originary thinking. A brief recollection of this project will precede the presentation of Heidegger's prognostic. After that presentation, I will attempt to show how the future predicated by Heidegger's prognostication may be seen to come forward through the poetics of originary thinking. Here, I will revisit some recent work I have done on originary thinking as poiein, or the making of more poetry, less prose in educational theory.